2019
DOI: 10.1002/jbmr.3674
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid-Targeted Overexpression of Regulator of G-Protein Signaling 5 (RGS5) Causes Hyperparathyroidism in Transgenic Mice

Abstract: The relationship between impaired calcium sensing, dysregulated parathyroid hormone (PTH) secretion, and parathyroid cell proliferation in parathyroid neoplasia is not understood. We previously reported that a GTPase activating protein, regulator of G‐protein signaling 5 (RGS5) is overexpressed in a subset of parathyroid tumors associated with primary hyperparathyroidism (PHPT) and that RGS5 can inhibit signaling from the calcium‐sensing receptor (CASR). In vivo, we found that RGS5‐null mice have abnormally lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 36 publications
0
7
0
2
Order By: Relevance
“…Deficient calcium sensing and disrupted feedback to PTH occur early in the pathogenic process of parathyroid cells’ hyperplastic expansion [ 14 ]. Koh et al have shown that abnormal upregulation of the Regulator Of G Protein Signaling 5 ( RGS5 ) gene can influence CaSR signaling in the PHPT [ 4 , 15 ]. Furthermore, vitro study has demonstrated that the Glial Cells Missing Transcription Factor 2 (GCM2) protein regulates the CaSR expression [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Deficient calcium sensing and disrupted feedback to PTH occur early in the pathogenic process of parathyroid cells’ hyperplastic expansion [ 14 ]. Koh et al have shown that abnormal upregulation of the Regulator Of G Protein Signaling 5 ( RGS5 ) gene can influence CaSR signaling in the PHPT [ 4 , 15 ]. Furthermore, vitro study has demonstrated that the Glial Cells Missing Transcription Factor 2 (GCM2) protein regulates the CaSR expression [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, vitro study has demonstrated that the Glial Cells Missing Transcription Factor 2 (GCM2) protein regulates the CaSR expression [ 16 ]. In PHPT, impaired calcium sensing results in elevated PTH secretion and parathyroid neoplasia [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…By creating the transgenic mouse with overexpression of RGS5 in the parathyroid gland, the authors found that these mice showed hyperparathyroidism and increased bone mass. Further, the forced overexpression of RGS5 in parathyroid cells impaired CASR signaling and negatively feedback on PTH secretion, demonstrating that RGS5 plays a critical role in bone formation through regulating PTH and CASR signaling (51).…”
Section: Effects Of Rgs Proteins In Bone Homeostasismentioning
confidence: 99%